Online teaching : tools and techniques to achieve success with learners - Casey, K. Michael; Shaw, Erin; Whittingham, Jeff; Gallavan, Nancy P. (Rowman & Littlefield, 2018)
"The purpose of this book is to equip online educators with tools, techniques, and tips to conduct a successful online learning experience, encompassing preparation, design, and facilitation of effective outcomes that benefit learners and educators. It is structured to guide and support the online educator from design and development to delivery" --